Degradation of 1.3 mu m InAs Quantum-Dot Laser Diodes: Impact of Dislocation Density and Number of Quantum Dot Layers - Buffolo, Matteo; Rovere, Lorenzo; De Santi, Carlo; Jung, Daehwan; Norman, Justin; Bowers, John E.; Herrick, Robert W.; Meneghesso, Gaudenzio; Zanoni, Enrico; Meneghini, Matteo (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This paper investigates the impact of dislocation density and active layer structure on the degradation mechanisms of 1.3 mu m InAs Quantum Dot ( QD) lasers for silicon photonics. We analyzed the optical behavior of two sets of samples, having different dislocation densities and different number of quantum dot layers in the active region. The samples were subjected to a short-term step-stress experiment and to long-term constant current operation in order to investigate the dominant degradation processes. The results indicate that: (i) the temperature stability is much higher in the devices grown on native substrate, thanks to the lower defect density; (ii) the roll-off current is considerably higher for the devices with higher number of layers, due to the lower density of carriers in the QDs; (iii) in nominal ground-state operating regime, the degradation rate is limited by the density of dislocations, that may serve as preferential paths for the diffusion of non-radiative recombination centers; (iv) at extreme injection levels and operating temperatures, the devices exhibit a blue shift of the spectral emission; possible explanations for this process are discussed in the paper.